Generation of friction-increasing surfaces by turn-milling. (August 2022) - Funke, Roman; Schanner, Jonathan; Hasse, Alexander; Schubert, Andreas
Abstract: Increasing the coefficient of static friction (COF) in frictional connections can help to respond to current demands such as increasing power density or lightweight design. Turn-milling is used to generate surfaces with protruding microstructures that lead in combination with a surface exhibiting a lower hardness to an increase of the COF. For the investigations, end faces of cylindrical specimens of the steel 1.7225 (42CrMo4) in quenched and tempered heat treatment condition (+QT) are machined using single-edged TiAlN coated cemented carbide end milling cutters. Four tool types varying in terms of the corner geometry are utilised in order to create different profile tip angles (PTAs) α pt of the microstructures: rounded ( r ε  = 0.2 mm), chamfered (0.2 mm × 45°) and two types of sharp corners with different tool included angles of ε r  = 88° and 75°. The influence of the process parameters feed per tooth f z, radial feed f rad and cutting speed v c on the surface topography and the COF are investigated using a 2 3 full factorial design with centre point for each corner type. The COF is determined with a special torsional test bench using face turned counterbodies made of the steel 1.0503 (C45). The PTA influences the ability of the profile tips to penetrate the surface of the counterbody but also their shear strength under a tangential load. Among the variants studied, microstructures with a PTA α pt  = 88° proved to be most effective in regard to an increase in the COF. However, the feed per tooth f z has a strong effect on the surface topography as well as on the COF for all tool types tested, but in particular for this PTA. A slight change of f z in the micrometer range results in strongly differentiated surface patterns. These differences can also be demonstrated by the peak material volume Vmp . This surface parameter shows the best correlation with the COF. The highest mean COF μ ¯ max = 0.69 is achieved with microstructures exhibiting a PTA of α pt  = 88° at the feeds f rad  = 0.2 mm and f z  = 0.125 mm.